(c+8)(8c+2)=(c+8)(8c+2)

Simple and best practice solution for (c+8)(8c+2)=(c+8)(8c+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (c+8)(8c+2)=(c+8)(8c+2) equation:



(c+8)(8c+2)=(c+8)(8c+2)
We move all terms to the left:
(c+8)(8c+2)-((c+8)(8c+2))=0
We multiply parentheses ..
(+8c^2+2c+64c+16)-((+8c^2+2c+64c+16))=0
We calculate terms in parentheses: -((+8c^2+2c+64c+16)), so:
(+8c^2+2c+64c+16)
We get rid of parentheses
8c^2+2c+64c+16
We add all the numbers together, and all the variables
8c^2+66c+16
Back to the equation:
-(8c^2+66c+16)
We get rid of parentheses
8c^2-8c^2+2c+64c-66c+16-16=0
We add all the numbers together, and all the variables
=0
c=0/1
c=0

See similar equations:

| 4x-3+5x=(x+3)2 | | 12x-6=67 | | .43x-2+4x=3(x+3) | | 64.95+45h=79.95 | | s+36=117 | | 5x+3÷3=8×-34÷2 | | 6x+12=98 | | 9x+3-x=4(x+3) | | 18y+3y-15y-2=10 | | 2(s+51)=(10s-13)+(4s+7) | | 12x-9=279 | | .20=1.3/x | | -6(x-7)=-8x+44 | | 14-7x=2(x+3) | | 9c-7c-c-c+4c=16 | | 2(-6y+68)=(y+5)+(2y+11) | | 7p^2+52p-32=0 | | |x+2|=-13 | | X/2+1/3-1=x/6+3x | | 52.37=y=109.67 | | 9x-4(3-2x)=5 | | 7x+26=-3(x-2) | | 10k-8k=6 | | 0x-9=3x+7 | | 2(-p+74)=(p+72)+(9p-68) | | 12q+3q-15q+2q=14 | | 4(v+4)=-4v-8 | | 39x+2=40x | | 6x-x-2-2=5x-2 | | H=-16t^2+256t+12 | | 8+7x+3=74 | | y+4y+y=18 |

Equations solver categories